Perancangan Media Sosialisasi Tanggap Bencana Kabupaten Semarang Berbasis Animasi 2D - Dian Iskandar; Anthony Y.M. Tumimomor (Universitas Negeri makassar, 2017)
Indonesia is an area prone to the occurrence of disasters, this can be caused by natural factors and human factors. Disasters that occur often cause the impact of material loss as well as loss of life. To minimize the losses from the occurrence of disasters it is necessary socialization of the community together in response to a threatening disaster. Therefore, this research will discuss about the design of socialization media of disaster response for the people of District Semarang based on 2D animation. The object of this research is the Regional Disaster Management Agency of District Semarang. This research uses qualitative methods and linear strategy, which contains the design of animation from the beginning to the final form of 2D animation video as a medium of disaster response socialization. The result is a disaster response socialization media presented in a 2D animation that contains information related to signs, prevention, and disaster management.Indonesia merupakan daerah rawan terjadinya bencana, hal ini bisa disebabkan oleh faktor alam dan faktor manusia. Bencana yang terjadi sering menyebabkan dampak kerugian material sekaligus hilangnya nyawa. Untuk meminimalisasi kerugian akibat terjadinya bencana maka diperlukan sosialisasi masyarakat bersama-sama dalam merespon bencana yang mengancam. Oleh karena itu, penelitian ini akan membahas tentang disain media sosialisasi tanggap bencana bagi masyarakat Kabupaten Semarang berdasarkan animasi 2D. Objek penelitian ini adalah Badan Penanggulangan Bencana Daerah Kabupaten Semarang. Penelitian ini menggunakan metode kualitatif dan strategi linier, yang berisi desain animasi dari awal hingga bentuk akhir video animasi 2D sebagai media bencana.